Inter-relations of core language, pragmatic language, and social competence in preschoolers - Lau, Clarissa (Research in Language, 2015)
Language skills provide preschoolers with the foundational skills needed to socially interact, but little is known about the relationship between specific language skills and broad constructs of social competence. Sixteen preschoolers between 3-5 years with varying language abilities were recruited. Descriptive and correlational analyses were conducted to examine the relationships between language and social competence. The main finding of this study showed that early literacy skills and word knowledge and retrieval were significantly correlated with Social Independence and Social Interaction respectively. These findings support the notion that the content of preschoolers’ conversations rather than the accuracy of their speech or syntax is associated with success in social interaction and social independence.